The force of time an introduction to Deleuze through Proust - Faulkner, Keith W. (Univ. Press of America, 2008)
Time is not normally visible. While we often sense the events in time, we overlook what Marcel Proust calls "time in a pure state." That's why, in The Force of Time, Keith W. Faulkner shows how Gilles Deleuze extracts his "ontology of the virtual" from Proust's psychological time. To prove this, he examines the ways these writers say we occupy time without counting it. In the end, he reveals not only how Proust influences Deleuze, but how we sense time as a force as well.
Keywords: Deleuze, Gilles <1925-1995>; Proust, Marcel <1871-1922>; Proust, Marcel -- 1871-1922; Deleuze, Gilles -- 1925-1995; Philosophie; Philosophy in literature; Time in literature; Time -- Philosophy